Advancing Sustainable Development in the Ghanaian e-Waste Sector: A System Dynamics Perspective - Vanessa Heinrich; Svenja Klose; Magnus Fröhling (Sustainable Development, 2025)
Ghana is a major e-waste treatment hotspot in the Global South, dominated by the informal sector (IFS). There, sustainable development goals (SDGs) like good health and well-being, no poverty, or sustainable communities remain an area of concern. Therefore, the present study aims at contributing to sustainable development in the Ghanaian IFS. To do so, for the first time, we apply the system dynamics methodology to the Ghanaian e-waste context. The center and strength of the study is a causal loop diagram (CLD) which was developed in a participatory process with stakeholders on-site. The CLD shows how none of the goals stands alone but is embedded in a dynamic relationship with other goals and with the actors and proposed measures in the system. The CLD can be used as a map when designing measures to understand potential consequences for actors and concurrent goals and measures.
Keywords: 330; causal loop diagram; e-waste; Ghana; informal sector; system dynamics